Online communication and collaboration via digital discussion forums: Impacts on 21st century skills and english language learning - Mazura, Jamalai@Jamali; Ruhil Amal, Azmuddin; Chand, Varun (Universiti Malaysia Sarawak, 2025)
The use of Digital Discussion Forums (DDFs) has not been researched sufficiently in English for Specific Purposes (ESP) courses to enhance communication and collaboration skills. Therefore, this paper explores the impact of DDFs usage on these skills through digital discussions among undergraduates. DDF was incorporated into an ESP language classroom and involves a group project outside of classroom time, namely, Company Profile (CP). The qualitative study involved 26 students enrolled in English for Business Professional Communication. Data were collected using semi-structured interviews and reflective journals. Thematic analysis was conducted and themes on critical components of 21st Century skills development were analysed. Inter-rater reliability analysis utilising Cohen Kappa analysis showed nearly perfect scores, indicating data reliability. The findings revealed a positive impact of online engagement on students’ overall communication and collaboration skills alongside their English language skill. The findings suggest the usefulness of DDF in developing communicative and collaborative skills.